A Rational Design of High‐Performance Sandwich‐Structured Quasisolid State Li–O2 Battery with Redox Mediator. Issue 23 (13th October 2017) - Liu, Kailiang; Sun, Hongguang; Dong, Shanmu; Lu, Chenglong; Li, Yang; Cheng, Junmei; Zhang, Jianjun; Wang, Xiaogang; Chen, Xiao; Cui, Guanglei
Abstract: The increasing interest in Li–O2 battery arises from its unparalleled theoretical energy density. Nevertheless, the poor reversibility of cathode reaction and unstable characteristic of Li anode hinder its further application. To address these issues, a high‐performance sandwich‐structured quasisolid polymer electrolyte (QSPE) is designed to meet the requirement of both cathode and anode. For the first time, lithiated Nafion ionomer (Li‐Nafion) is introduced into Li–O2 cell to separate "catholyte" and "anolyte." Redox mediator (RM) is introduced into gel‐like catholyte, based on polymethymethacrylate, to achieve high capacity and reversibility. Polypropylene carbonate is chosen as solid‐state anolyte for enhancing interface stability of lithium anode. It is demonstrated that the QSPE exhibits excellent permselectivity to block RM shuttling, as well as good ionic conductivity and high electrochemical window. A solution mechanism formation of discharge product is demonstrated in the Li–O2 cell with QSPE and the RM works well for cycles at room temperature. This sandwich‐structured design strategy will provide a new pathway to promote the properties of Li–O2 battery. Abstract : A sandwich‐structured quasisolid polymer electrolyte is designed to separate cathode reaction with lithium anode in Li–O2 batteries application. A gel‐like catholyte with redox mediator (tetramethyl piperidine) endows the cell with high capacity and reversibility. The shuttling effect of redox mediator has been limited effectively by lithiated Nafion ionomer and polypropylene‐carbonate‐based solid‐state anolyte.